2015
DOI: 10.1038/ncomms7517
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of the intestinal epithelium by the MSI2 RNA-binding protein

Abstract: The MSI2 RNA binding protein is a potent oncogene playing key roles in hematopoietic stem cell homeostasis and malignant hematopoiesis. Here we demonstrate that MSI2 is expressed in the intestinal stem cell compartment, that its expression is elevated in colorectal adenocarcinomas, and that MSI2 loss of function abrogates colorectal cancer cell growth. MSI2 gain of function in the intestinal epithelium in a drug inducible mouse model is sufficient to phenocopy many of the morphological and molecular consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
193
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(199 citation statements)
references
References 51 publications
6
193
0
Order By: Relevance
“…S6 A, B, E, and F). However, the claudin mRNAs lack [(G/A)U(n)AGU (n = 1-3)] the consensus motifs for MSI2 binding described in Wang et al (28), suggesting direct regulation of translation is not involved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S6 A, B, E, and F). However, the claudin mRNAs lack [(G/A)U(n)AGU (n = 1-3)] the consensus motifs for MSI2 binding described in Wang et al (28), suggesting direct regulation of translation is not involved.…”
Section: Resultsmentioning
confidence: 99%
“…Although a number of studies have previously identified a role for the MSI2 paralogue MSI1 as oncogenic in a number of cancer types (30)(31)(32), MSI2 has attracted much less scrutiny. However, MSI2 has been shown to be oncogenic in a mouse model of colon cancer (28); MSI2 expression is induced by loss of the adenomatous polyposis coli (APC) gene, and overexpression of MSI2 phenocopies APC loss (28). MSI2 is also overexpressed and oncogenic in human leukemias.…”
Section: Discussionmentioning
confidence: 99%
“…For example, APC can bind RNA and regulate the microtubule scaffold (50). Furthermore, the loss of Apc leads to the upregulation of Musashi proteins, which are pleiotropic translational regulators that affect numerous important signaling cascades, including the mTorc1 pathway (51,52). Second, characteristic for the deletion of Cnsk1a1 (but not Apc) induction of the DNA damage response, activation of the p53-driven genes, and cell senescence are likely augmented by IFN signaling activated by CK1␣ deletion.…”
Section: Discussionmentioning
confidence: 99%
“…The studies summarized above tie expression of MSI1 and MSI2, at least indirectly, to factors linked to maintenance of stem cell characteristics or induction of cancer. These include loss of APC and induction of TCF/LEF binding in colon cancer (37,38), and repression by KLF4 in pancreatic cancer (24). MSI1 expression, along with other stem cell markers, was negatively regulated in GBM xenografts and in depleted stem-like GBM cells treated with the c-MET inhibitor crizotinib (39).…”
Section: Control Of Musashi Protein Expressionmentioning
confidence: 99%